2015
DOI: 10.1099/jgv.0.000288
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus type 1 splicing at the major splice donor site is controlled by highly conserved RNA sequence and structural elements

Abstract: Human immunodeficiency virus type 1 (HIV-1) splicing has to be strictly controlled to ensure the balanced production of the unspliced and all differently spliced viral RNAs. Splicing at the major 59 splice site (59ss) that is used for the synthesis of all spliced RNAs is modulated by the local RNA structure and binding of regulatory SR proteins. Here, we demonstrate that the suboptimal sequence complementarity between this 59ss and U1 small nuclear RNA (snRNA) also contributes to prevent excessive splicing. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…For example, the frequently observed double variation C287A/U288C opens two bps (bp 5 and 6: C 287 –G 294 and U 288 –A 293 ) but results in the formation of two alternative bps (A 287 –U 295 and C 288 –G 294 ). Some virus isolates hold multiple nt differences in this leader RNA domain, but as previously shown [ 15 , 17 ] most isolates can fold a similar SD hairpin structure. Only a minority of the variations does not allow Watson-Crick bp formation.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…For example, the frequently observed double variation C287A/U288C opens two bps (bp 5 and 6: C 287 –G 294 and U 288 –A 293 ) but results in the formation of two alternative bps (A 287 –U 295 and C 288 –G 294 ). Some virus isolates hold multiple nt differences in this leader RNA domain, but as previously shown [ 15 , 17 ] most isolates can fold a similar SD hairpin structure. Only a minority of the variations does not allow Watson-Crick bp formation.…”
Section: Resultsmentioning
confidence: 89%
“…Mutation-reversion analysis of the lower stem of the TAR hairpin indeed indicated that maintenance of the structure is more critical than the sequence requirement [ 12 ]. Conservation of the SD sequence is likely related to the presence of the U1 snRNA and SR protein binding sites [ 16 , 17 , 30 , 53 ]. These sequence requirements may have prevented the evolution of more informative sequence variation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations